Day and night changes in energy expenditure of patients on automated peritoneal dialysis. Issue 5 (May 2021) - Aniort, Julien; Montaurier, Christophe; Poyet, Anais; Meunier, Nathalie; Piraud, Aurélien; Aguilera, Didier; Bouiller, Marc; Enache, Ioana; Ali, Youssef; Jouve, Christelle; Blot, Adeline; Farigon, Nicolas; et al.
Summary: Rationale: Automated peritoneal dialysis (APD) treatment for end-stage kidney disease affords patients a degree of autonomy in everyday life. Clinical investigations of their energy expenditure (EE) are usually based on resting EE, which could mask day and night variations in EE. The aim of this study, therefore, was to compare the components of EE in APD patients and healthy control (C) subjects. Material and method: Patients treated with APD for more than 3 months were compared with C volunteers matched for age and lean body mass (LBM). Biochemical analyses were performed and body composition was determined by DEXA to adjust EE to LBM. Total EE, its different components and respiratory quotients (RQ) were measured by a gas exchange method in calorimetric chambers. Spontaneous total and activity-related EE (AEE) were also measured in free-living conditions over 4 days by a calibrated accelerometer and a heart rate monitor. Results: APD (n = 7) and C (n = 7) patients did not differ in age and body composition. REE did not differ between the two groups. However, prandial increase in EE adjusted for dietary energy intake was higher in APD patients (+57.5 ± 12.71 kcal/h) than in C subjects (+33.8 ± 10.5 kcal/h, p = 0.003) and nocturnal decrease in EE tended to be lower in APD patients undergoing dialysis sessions (- 4.53 ± 8.37 kcal/h) than in subjects (- 11.8 ± 7.69 kcal/h, p = 0.059). Resting RQ (0.91 ± 0.09 vs 0.81 ± 0.04, p = 0.032) and nocturnal RQ (0.91 ± 0.09 vs 0.81 ± 0.04, p = 0.032) were significantly higher in APD patients, indicating a preferential use of glucose substrate potentially absorbed across the peritoneum. AEE was lower in APD patients (595.9 ± 383.2 kcal/d) than in C subjects (1205.2 ± 370.5 kcal/d, p = 0.011). In contrast, energy intakes were not significantly different (1986 ± 465 vs 2083 ± 377 kcal/d, p = 0.677). Conclusion: Although the two groups had identical resting EE, APD patients had a higher prandial increase in EE, a lower activity-related EE and higher resting and nocturnal RQ than healthy subjects.